Mathematics in Context. An Interview with Patricia Camarena Gallardo - René Pinet Plasencia (Universidad Autónoma de Baja California, 2005)
In this interview Dr. Patricia Camarena tells about the development and application in Mexico of one of the most significant breakthroughs in math teaching. The group she coordinates at Instituto Politécnico Nacional (ipn) has worked in strengthening the math curriculum of engineering at ipn.